Assessment of the psychophysiological compatibility of sports team members - Golub, Ya.V.; Medvedeva, E.N.; Baryaev, A.A.; Soboleva, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyze modern approaches to assessing psychophysiological compatibility and correcting teamwork among sports team members. Methods and structure of the study. The object of the study was domestic and foreign scientific literature on the problem of psychophysiological compatibility in sports. To achieve this goal, theoretical research methods were used: analysis and synthesis; abstraction; induction and deduction. Results and conclusions. Based on a comparative analysis of existing hardware methods for assessing psychophysiological compatibility, requirements for approaches that improve the quality of monitoring and correction of athletes' teamwork have been formulated. The conclusion is made about the importance of taking into account the psychophysiological level of compatibility and suggests ways to improve the technology of its measurement to improve performance in team and group sports.